FRI0012 Rituximab in the Treatment of Patients with Rheumatoid Arthritis Related Lung Disease. (10th June 2014) - Iqbal, K.; Kelly, C.; Saravanan, V.; Rynne, M.; Hamilton, J.; Heycock, C.
Abstract : Background: There is little evidence to guide clinicians on which biologic agent to use in patients with active rheumatoid arthritis (RA) in the presence of lung disease. Both interstitial lung disease (ILD) and bronchiectasis (BR) commonly complicate RA and there are sound theoretical concerns about the potential for biologic therapy to adversely affect these conditions. Experience with anti-TNF drugs in such patients indicate a significant risk of accelerated respiratory failure in RA-ILD and an increase in lung infections in RA-BR. The effect of B cell monotherapy on pulmonary manifestations of RA is less well established. Objectives: To assess the articular and pulmonary response to pulsed intravenous rituximab monotherapy in the treatment of patients with RA and associated lung disease Methods: We assessed the use of Rituximab in 50 patients with RA from one hospital. We collected data on all comorbidity and divided the patients into two groups based on whether they had evidence of RA with lung disease (ILD and/or BR) or not. We collected and analysed demographic data together with duration of rituximab and all other drug therapy. We assessed the effect of Rituximab on the disease activity score by comparing values at baseline and at present, and compared the outcomes between those with and without lung disease. In those with lung disease, we assessed the effect of rituximab on lung vital capacity (VC) and gas transfer (TLco) over the same time period. Results: Among 50 patients with RA treated with rituximab over a five year period, 20 had evidence of lung disease. There were no significant differences in age, duration of treatment or gender mix between those with and without lung disease and only one death was recorded. Patients with lung disease were more likely to receive rituximab alone or with mycpophenolate, while those without lung disease more often had methotrexate. Mean DAS fell from 5.8 at baseline to 3.2 after treatment, with no differences between those with and without lung disease. Patients with ILD and BR tolerated treatment well and mean VC and gas transfer remained stable throughout treatment. Conclusions: Rituximab is an effective therapy for active articlar disease in patients with RA and associated lung disease. No specific adjustments were required in such patients and the drug was well tolerated with just one death from emphysema. Lung function tests remained stable on therapy. Our data suggests that rituximab should be considered as an alternative to anti-TNF therapy in RA patients with lung disease requiring biologic therapy for active articular disease. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2345